Oxford textbook of psychotherapy - Gabbard, G.O. Glen O.; Beck, J. S. Judith S.; Holmes, J. Jeremy (Oxford University Press, 2007)
With the publication of this book psychotherapy finally arrives at the mainstream of mental health practice. This volume is an essential companion for every practising psychiatrist, clinical psychologist, psychotherapy counsellor, mental health nurse, psychotherapist, and mental health practitioner. It is integrative in spirit, with chapters written by an international panel of experts who combine theory and research with practical treatment guidelines and illustrative case examples to produce an invaluable book. Part One gives a comprehensive account of all the major psychotherapeutic approaches. Parts Two and Three systematically describe psychotherapeutic approaches to the major psychiatric disorders and personality disorders. Many chapters are multi-authored and describe the psychodynamic, cognitive behavioural and other approaches for treating these illnesses. Part Four examines applications and modifications of psychotherapy across the lifecycle. Part Five describes psychotherapy with specific populations such as medical patients and those where gender is an issue, and finally Part Six tackles some of the special topics of concern to psychotherapists including ethics, legal issues, and psychotherapy and neuroscience. The first of its kind, this is a 'must have' volume for all trainee and practising psychological therapists, whatever their background - psychiatry, psychology, social work, or nursing.